Microsoft Visual C# 2010 step by step - Sharp, John, 1964- (Redmond, Wash. : Microsoft Press ; New Delhi : Dreamtech, 2010)
Your hands-on, step-by-step guide to the fundamentals of Visual C# development. This tutorial provides practical, learn-by-doing exercises for mastering C# language features and creating working applications and components for Windows-- back cover.
Pt.1. Introducing Microsoft Visual C# and Microsoft Visual Studio 2010. Welcome to C# -- Working with variables, operators, and expressions -- Writing methods and applying scope -- Using decision statements -- Using compound assignment and iteration statements -- Managing errors and exceptions -- Pt. 2. Understanding the C# language. Creating and managing classes and objects -- Understanding values and references -- Creating value types with enumerations and structures -- Using arrays and collections -- Understanding parameter arrays -- Working with inheritance -- Creating interfaces and defining abstract classes -- Using garbage collection and resource management -- Pt. 3. Creating compounds. Implementing properties to access fields -- Using indexers -- Interrupting program flow and handling events -- Introducing generics -- Enumerating collections -- Querying in-memory data by using query expressions -- Operator overloading -- Pt. 4. Building Windows presentation foundation applications. Introducing Windows presentation foundation -- Gathering user input -- Performing validation -- Pt. 5. Managing data. Querying information in a database -- Displaying and editing data by using the entity framework and data binding -- Pt. 6. Building professional solutions with Visual Studio 2010. Introducing the task parallel library -- Performing parallel data access -- Creating and using a web service -- Appendix: Interoperating with dynamic languages.
Includes 1 CD-ROM in pocket at back of book.
Includes index.
Keywords: C# (Computer program language); Visual programming (Computer science)